Pencatatan Tanah Wakaf di Pimpinan Cabang Persis Menurut UU 41 Tahun 2004 - Roni Hermawan (Jurnal Riset Hukum Keluarga Islam, 2023)
Abstract. The recording of waqf land is a sensitive and complex issue that can lead to disputes and conflicts. Law No. 41 of 2004 stipulates that waqf must be recorded to obtain authentic evidence and in Surah Al-Baqarah: 282 regarding recording in muamalah. The purpose of this research is to find out the recording of waqf land in PC Persis Pangalengan District according to Law No. 41 of 2004 and Islamic law. This research method is qualitative and uses a normative juridical approach. Primary data consists of interviews, secondary data consists of primary legal materials such as laws, PP, KHI, books, journals. while tertiary data consists of websites, and other sources of information. Data analysis consists of recording waqf land in PC Persis Pangalengan District according to Law No. 41 of 2004 and Islamic Law, verified, and conclusions drawn. The first research result shows that the process of recording waqf land in PC Persis Pangalengan District still does not comply with the laws and regulations because many assets have not been recorded. This should be done to obtain authentic evidence so as not to cause problems. Second, the recording of waqf land in PC Persis Pangalengan Subdistrict is valid according to Islam, but judging from the procedures in carrying out waqf, it has not been fulfilled because there are still many waqf assets that are not recorded before the PPAIW and recorded at the KUA. Abstrak. Pencatatan tanah wakaf adalah masalah yang sensitif dan kompleks yang dapat menyebabkan perselisihan dan konflik. Dalam UU No. 41 Tahun 2004 menetapkan bahwa wakaf harus dicatat untuk mendapatkan bukti otentik dan dalam Surah Al-Baqarah:282 mengenai pencatatan dalam muamalah. Tujuan penelitian ini adalah untuk mengetahui pencatatan tanah wakaf di PC Persis Kecamatan Pangalengan menurut UU No. 41 Tahun 2004 dan hukum Islam. Metode penelitian ini adalah kualitatif dan menggunakan pendekatan yuridis normatif. Data primer terdiri dari wawancara, data sekunder terdiri dari bahan hukum primer seperti UU, PP, KHI, buku, jurnal. sedangkan data tersier terdiri dari website, dan sumber informasi lainnya. Analisis data terdiri dari pencatatan tanah wakaf di PC Persis Kecamatan Pangalengan menurut UU No. 41 Tahun 2004 dan Hukum Islam, diverifikasi, dan ditarik kesimpulan. Hasil Penelitian Pertama, menunjukkan bahwa proses pencatatan tanah wakaf di PC Persis Kecamatan Pangalengan masih banyak yang tidak mematuhi peraturan perundang-undangan karena banyak aset yang belum tercatat. Hal tersebut harusnya dilakukan untuk mendapatkan bukti otentik agar tidak menimbulkan masalah. Kedua, pencatatan tanah wakaf di PC Persis Kecamatan Pangalengan sudah sah menurut Islam, namun dilihat dari prosedur dalam melakukan wakaf belum memenuhi karena masih banyak aset wakaf yang tidak dicatatkan di hadapan PPAIW dan tercatat di KUA.